Auswirkungen des gesetzlichen Mindestlohns auf Betriebe und Unternehmen - Mario Bossler; Nicole Gürtzgen; Eric-Benjamin Börschlein (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
Der vorliegende erste Projektbericht enthält die Ergebnisse des Forschungsprojektes "Auswirkungen des gesetzlichen Mindestlohns auf Betriebe und Unternehmen". Das Forschungsprojekt wird durch das Institut für Arbeitsmarkt- und Berufsforschung (IAB) im Auftrag der Mindestlohnkommission durchgeführt. Im Mittelpunkt des Berichts stehen detaillierte empirische Analysen der Effekte der Einführung und der ersten Erhöhung des gesetzlichen Mindestlohns auf unterschiedliche betriebliche Ergebnisgrößen. Das zentrale Analyseinstrument bildet dabei der Differenz-in-Differenzen-Ansatz, welcher im vorliegenden Bericht größtenteils auf der Betriebsebene angewandt wird. Der empirischen Analyse vorgelagert ist die detaillierte Beschreibung der empirischen Vorgehensweise sowie der verwendeten Datengrundlagen. Abschließend erfolgt eine Zusammenfassung der Ergebnisse sowie ein Ausblick auf künftige Analysen mindestlohnbedingter Anpassungsreaktionen. Während die Analysen auf Basis des IAB-Betriebspanels einen moderaten negativen Effekt der Einführung des Mindestlohns auf die betriebliche Beschäftigung zeigen (ca. -88.000 Beschäftigungs-verhältnisse), ist der Effekt der ersten Mindestlohnerhöhung im Jahr 2017 für die davon betroffenen Betriebe tendenziell positiv (ca. +39.000 Beschäftigungsverhältnisse). Der positive Effekt der Anhebung erscheint allein deswegen plausibel, weil die Anhebung im Reallohn nur 0,9 Prozent (jährlich) ausmacht, während sich der Arbeitsmarkt auch im Niedriglohnsegment positiv entwickelt hat. Insgesamt wird der Beschäftigungseffekt bis zum Jahr 2018 auf einen Rückgang von (hochgerechnet) 49.000 Beschäftigungsverhältnissen beziffert, wobei der Effekt insbesondere durch Anpassungen von Betrieben in Ostdeutschland und Betriebe, die sich einem hohen Wettbewerbsdruck ausgesetzt fühlen, hervorgerufen wird. In monopsonistischen Branchen ist der Effekt jedoch vergleichsweise gering. Für die speziellen Beschäftigungsgruppen der Leiharbeitenden, freien Mitarbeiterinnen und Mitarbeitern, sowie Praktikantinnen und Praktikanten wurden empirisch keine nennenswerten Beschäftigungseffekte des Mindestlohns nachgewiesen. Analysen der gesamtwirtschaftlichen Arbeitsnachfrage mit der IAB-Stellenerhebung deuten auf keinen signifikanten Effekt des Mindestlohns auf die Anzahl offener Stellen hin. [...] – – This report contains the results of the research project "Effects of the statutory minimum wage on establishments and enterprises". The project is carried out by the Institute for Employment Re-search (IAB) on behalf of the German Minimum Wage Commission. The report focuses on detailed empirical analyses of the effects of the introduction and the first increase of the statutory mini-mum wage in Germany on various establishment-level outcomes. The empirical analysis is mainly based on the difference-in-differences approach, which is largely applied at the establishment level. Prior to the empirical analysis, we provide a detailed description of the empirical methodol-ogy and the data. Concluding the report, we give a summary of the results and an outlook on future analyses of minimum wage related adjustment reactions. While the analyses based on the IAB Establishment Panel show a moderate negative effect of the minimum wage introduction on employment (approx. -88,000 employment relationships), the ef-fect of the first minimum wage increase in 2017 tends to be positive for the affected establishments (approx. +39,000 employment relationships). The positive effect of the minimum wage increase seems to be plausible because the increase in real wages is only 0.9 percent (annually), while the labor market developed positively in the low-wage segment. The overall employment effect is extrapolated to a decline of 49,000 jobs by 2018, while the effect is particularly concentrated on es-tablishments in Eastern Germany and employers that feel exposed to high competitive pressure. In monopsonistic industries, however, the effect is relatively small. For special employment groups including temporary workers, freelancers and interns, we cannot empirically verify a significant employment effect of the minimum wage. Analyses of the overall labor demand with the IAB Job Vacancy Survey do not indicate a significant effect of the minimum wage on the number of vacancies. With regard to profitability of establishments, the analyses show a significant negative impact of the introduction of the minimum wage, but do not provide evidence of any significant effects of the first minimum wage increase. The profitability-decreasing effect of the introduction of the min-imum wage is mainly due to the increase in operational personnel costs. At the same time, the analyses do not show any significant effect on the productivity of the affected establishments, indicating that the affected establishments did not compensate the minimum wage by increasing the productivity of their employees. Analyses of the effects of the minimum wage on investments in physical and human capital show significant negative effects in the short run for the year after the introduction of the minimum wage. Affected establishments initially reduced their investment levels right after the introduction of the minimum wage, but they did not show any minimum wage-related adjustment in their investment behavior in the following years. However, we clearly observe a structural difference that already existed before the minimum wage was introduced or increased. Establishments not affected by the minimum wage invest considerably more in physical capital and in the training of their employees. Effects on the share of apprentices and the number of apprenticeship training positions offered or filled are neither found for the minimum wage introduction nor for the first minimum wage increase. Consequently, investments in apprenticeship training were not reduced because of increased personnel costs. The results also do not indicate any effects of the introduction or increase of the minimum wage on integration or outsourcing activities of establishments or on the share of intermediate inputs in the production process.
Keywords: 330; Mindestlohn; Beschäftigungseffekt; Deutschland